The ethics of aboriginal health research : an annotated bibliography - McAullay, Daniel; Anderson, Ian.; Griew, Robert; VicHealth Koori Health Research and Community Development Unit. (Parkville, Vic. : VicHealth Koori Health Research and Community Development Unit, 2002)
A bibliography of Australian and international literature on the ethical issues relating to research in Indigenous populations; a brief summary of the issues identified in the literature is provided as a guide to the annotated bibliography; consultation and community involvement; collaborative research.
"January 2002"
Keywords: Medicine -- Research -- Bibliography; Aboriginal Australians -- Health and hygiene -- Research -- Moral and ethical aspects; Health; Research - Methodology and techniques; Research - Ethics; Libraries - Reference materials - Bibliographies